Hubungan Tingkat Stres Dengan Prestasi Akademik Mahasiswa : RELATIONSHIP BETWEEN STRESS LEVELS AND STUDENTS' ACADEMIC ACHIEVEMENT - Siagian, Ira Ocktavia; Linda, Sok; Melia, Stephanie (Jurnal Keperawatan Muhammadiyah, 2025)
Stress can be experienced in every human being and has a negative impact. For students, stress can stem from a variety of stressors, such as the pressure to succeed academically or think about a future that is not yet on track, or family problems. Students are also exposed to social, physical, and academic life and may have an impact on their academic performance. Student academic achievement is measured using the Cumulative Grade Point Average (GPA). This study aims to determine the relationship between stress levels and academic achievement of biology students. The research was conducted at the immanuel health institute from May to August 2024. The research method used is a correlational study. The population of this study is all students. The sample used in this study was 136 students who were taken by Simple Random Sampling. And the data analysis technique Using Rank Spearman Based on the results, it shows that from the results of the study, the frequency distribution based on gender is almost entirely from the respondents (87.5%) female, the frequency based on the study program is almost half of the respondents (39.7%) S1 Nursing and the frequency based on the estimate of almost half of the respondents (40.4%) in 2023, above obtained the distribution of student stress levels almost entirely from the respondents having stress levels light (79.4%), above this, the distribution of student academic achievement was obtained by half of the respondents moderately (50.0%). Based on the results of the study, it is known that under 136 student respondents who have the results of the Sprearman Rank test that has been carried out are corrected if the p-value is 0.118 ≥ 0.05, then Ha is accepted, which shows that there is no relationship between stress levels and student academic achievement at the Immanuel Institute of Health.